Pengaruh Berkumur Dengan Larutan Teh Hijau dan Teh Hitam Terhadap pH Saliva - Fika Melinda Putri; Susi Susi; Desy Purnama Sari (Faculty of Dentistry Universitas Andalas, 2019)
The prevalence of caries in Indonesia has increased by 53.53% from 2013 to 2018. Low salivary pH (potential of Hydrogen) is one of the main causes of dental caries. Acid as metabolic product of oral microorganism can decrease the salivary pH. The purpose of this paper is to determine the effect of gargling with green and black tea solutions on salivary pH. The increasing of salivary pH linear to salivary secretion. Gargling with green tea or black tea is one of the ways that can increase salivary secretion and pH by provides a mechanical and chemical stimulus to the oral cavity. Green tea and black tea contain polyphenols (catechins) which can increase salivary pH. Conclusion is gargling with green tea and black tea solutions can add salivary pH. Gargling with green tea is more effective to increase salivary pH than black tea. Green tea has a higher catechins content than black tea, in order to anti-cariogenic and anti-bacterial properties are more common in green tea.